2018
DOI: 10.1111/joim.12742
|View full text |Cite
|
Sign up to set email alerts
|

CCL23 is a promising biomarker of injury in patients with ischaemic stroke

Abstract: http://onlinelibrary.wiley.com/doi/10.1111/joim.12738/full.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The nine biomarkers identified in the present study were previously reported in ischemic stroke which involved the process of inhibiting development of atherosclerotic plaques, vascular remodeling, neural regeneration, and inflammatory response [ 16 25 ]. For example, IGFBP-6 and IL-5 were reported to be associated with inhibiting development of atherosclerotic plaques [ 26 29 ], LYVE-1 and PDGF-AA were beneficial to vascular remodeling and neural regeneration, respectively [ 16 – 18 ], while CCL-23, CXCL-12, ST-2, and TNF-α were reported to promote and worsen the inflammatory response: CCL-23, CXCL-12, and TNF-α played pro-inflammatory role [ 19 21 ], while ST-2 prevented anti-inflammatory effect of IL-33 [ 22 , 23 ]. In addition, PAI has an effect on inhibiting fibrinolysis in patients treated with tissue plasminogen activator [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nine biomarkers identified in the present study were previously reported in ischemic stroke which involved the process of inhibiting development of atherosclerotic plaques, vascular remodeling, neural regeneration, and inflammatory response [ 16 25 ]. For example, IGFBP-6 and IL-5 were reported to be associated with inhibiting development of atherosclerotic plaques [ 26 29 ], LYVE-1 and PDGF-AA were beneficial to vascular remodeling and neural regeneration, respectively [ 16 – 18 ], while CCL-23, CXCL-12, ST-2, and TNF-α were reported to promote and worsen the inflammatory response: CCL-23, CXCL-12, and TNF-α played pro-inflammatory role [ 19 21 ], while ST-2 prevented anti-inflammatory effect of IL-33 [ 22 , 23 ]. In addition, PAI has an effect on inhibiting fibrinolysis in patients treated with tissue plasminogen activator [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on functional enrichment analysis, mononuclear cell migration, receptor ligand activity, platelet alpha granule lumen, and cytokine-cytokine receptor interaction were significantly enriched items. After brain injury, CCL-23 and CXCL-12 modulate immune response through promoting migration of monocytes to the local sites of injury [ 19 , 20 ]. As the result of monocytes migration, inflammatory cytokines released from microglia, such as TNF-α, modulate infarct evaluation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCL23 has been reported to be associated with brain injury, immune response, systemic sclerosis, rhinosinusitis and other diseases [ 11 , 36 , 37 ]. However, to the best of our knowledge, the study of CCL23 and HCC has been limited to network data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…and PDGF-AA were bene cial to vascular remodeling and neural regeneration, respectively, [20][21][22] while CCL-23, CXCL-12, ST-2, and TNF-α were reported to promote and worsen the in ammatory response: CCL-23, CXCL-12, and TNF-α played pro-in ammatory role; [23][24][25] and ST-2 prevented anti-in ammatory effect of IL-33. [26][27] In addition, PAI has an effect on inhibiting brinolysis in patients treated with tissue plasminogen activator.…”
Section: Discussionmentioning
confidence: 99%
“…Contributing to the in ammation after brain injury, CCL-23 and CXCL-12 modulate immune response through promoting migration of monocytes to the local sites of injury. [23][24] As the result of monocytes migration, releasing in ammatory cytokines from microglia, such as TNF-α, modulate infarct evaluation. 25 It is worthy to note that these cytokines seemed contradictory with ENI given their proin ammatory effects.…”
Section: Discussionmentioning
confidence: 99%